THE SOCIOCULTURAL FACTORS INFLUENCING THE STUDY OF KOREAN HISTORY IN INDONESIA - ROSTINEU, Rostineu (International Journal of Korean Humanities and Social Sciences, 2021)
The historic event of the Korean Youth Independent Movement during the Japanese colonial period in Indonesia, which involved soldiers from Korea, has become a point of interest for Indonesian people, especially Indonesian millennials and historians. Since Indonesia’s independence from the Japanese colonial rule in 1945, Indonesia has gone through various difficulties and faced political crises, just as Korea has. This article discusses the social and cultural factors, particularly Indonesian millennials’ activities and interests which influence the study of Korean history in Indonesia. At several points, this research shows that the millennials’ mastery of the Korean language is important for the development of Korean historical studies in Indonesia. Applying the desk review method, this research finds a great interest among Indonesian millennials to study Korean history. One of the encouraging factors is the role of Korean history reviewers who bring Korean historical sources closer to Indonesian audiences through seminars that are intended for not only scholars, but also other millennials and the general public. The growth of Korean language users should be an important instrument to further develop not only the study of Korean history, but also diplomatic relations between Korea and Indonesia.